A short history of structural linguistics - Matthews, P. H. (Peter Hugoe) (Cambridge University Press, 2001)
This book is a concise historical survey of structural linguistics, charting its development from the 1870s to the present day. Peter Matthews examines the beginnings of structuralism and analyzes the vital role played in it by the study of sound systems and the problems of how systems change. He discusses theories of the overall structure of a language, the 'Chomskyan revolution' in the 1950s, and the structuralist theories of meaning. The book includes exposition, in particular, of the contributions of Saussure, Bloomfield and Chomsky.